Point‐of‐use carbon‐block drinking water filters change gut microbiome of larval zebrafish. Issue 4 (6th May 2022) - Wu, Chia‐Chen; Connell, Mackenzie; Zarb, Audrey; Akemann, Camille; Morgan, Stephanie; McElmurry, Shawn P.; Love, Nancy G.; Baker, Tracie R.
Summary: Activated carbon block (ACB) point‐of‐use (PoU) drinking water filters can change the bacterial composition in drinking water. Consuming ACB PoU filtered water may also influence gut microbiomes. This study uses the zebrafish model to evaluate how the ACB PoU filter affects the gut microbiomes and phenotypic responses in larvae and adulthood. An ACB PoU filter manifold system was constructed to feed larval and adult zebrafish tap and filtered water at the early and late stages of the filter operation period. Adult zebrafish gut microbiomes were not affected by exposure to water types and filter stages. Unlike the adult, gut microbiomes of the larvae exposed to filtered water at the late stage of filter operation were dominated by more filter‐relevant bacterial taxa, including Comamonadaceae and Brevundimonas, than the early stage‐filtered‐water‐ and tap water‐exposed larvae. We also found some fish that were either exposed to filtered water at early and late stages or tap water supplied to the filter toward the end of the experiment showed hyperactive locomotion behaviour, and had significantly lower relative abundances of a Pseudomonas spp. (OTU3) than the normally behaved fish. Our findings indicate that ACB PoU filtered water can alter gut microbiomes and affect the behaviour patterns in larval zebrafish.